Análise das barreiras comerciais sobre a inserção da agricultura paranaense no mercado externo: reflexos da crise internacional de 2008 - Campos, Lediany Freitas de (2013)
This study aims to analyze the impact of trade barriers on the inclusion of Paraná s agriculture in foreign market in the period 2000-2011, with emphasis on the effects of the international crisis of 2008. For the development of the research object, one opted for a quantitative approach, using descriptive statistical method and the gravity model. It was found that Paraná has, on average, about 50% of its exports based on agricultural products and it increased to 64.01% in 2011. Twelve major products represent around 90% of agricultural exports and in 2011 were responsible for 56.42% of general exports. Over the last decade, the target markets migrated from the European Union to Asia, with great emphasis to China. As for trade barriers, it was found that the agriculture of Paraná faces tariffs and Non-Tariff Barriers (NTB) by all importing countries analyzed. The tariff applied varies greatly in relation to the country and products. The NTB faced are diverse, and the most frequently applied are sanitary and phytosanitary barriers, followed by technical barriers. Agricultural subsidies applied by OECD countries have high variance around the average and tended to decrease over the period. In the year immediately following the 2008 international crisis, its repercussions were: declines in agricultural exports by volume and value of exports; declines for 10 of the top 12 products analyzed; variations in tariffs, both for more and for less; increase in agricultural subsidies; and the incidence of more BNT on agricultural products. By gravitational model, one evidenced that there is a negative relationship of Paraná s agricultural exports with trade tariffs, converging with the theory of international trade. A trade liberalization through tariffs, as a tariff reduction of 1%, would be positive at 3.7% for greater inclusion of state agriculture in the foreign market.